ICTV Virus Taxonomy Profile: Hepadnaviridae. (14th June 2020) - Magnius, Lars; Mason, William S.; Taylor, John; Kann, Michael; Glebe, Dieter; Dény, Paul; Sureau, Camille; Norder, Heléne; ,
Abstract : The family Hepadnaviridae comprises small enveloped viruses with a partially double-stranded DNA genome of 3.0–3.4 kb. All family members express three sets of proteins (preC/C, polymerase and preS/S) and replication involves reverse transcription within nucleocapsids in the cytoplasm of hepatocytes. Hepadnaviruses are hepatotropic and infections may be transient or persistent. There are five genera: Parahepadnavirus, Metahepadnavirus, Herpetohepadnavirus, Avihepadnavirus and Orthohepadnavirus . This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Hepadnaviridae, which is available at ictv.global/report/hepadnaviridae .